2015
DOI: 10.1007/s12264-014-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring prefrontal cortex functions in healthy humans by transcranial electrical stimulation

Abstract: The prefrontal cortex is involved in a multitude of cognitive, emotional, motivational, and social processes, so exploring its specifi c functions is crucial for understanding human experience and behavior. Functional imaging approaches have largely contributed to the enhancement of our understanding, but might have limitations in establishing causal relationships between physiology and the related psychological and behavioral processes. Non-invasive electrical stimulation with direct or alternating currents c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 81 publications
1
39
0
Order By: Relevance
“…While brain stimulation targeting specific brain areas was put forward as a tool to allow for causal neuroscience (Kuo and Nitsche, 2015), our data does not exclude such possibility, but suggests that a better understanding of local and particularly remote neurophysiological effects (e.g. as shown during cathodal M1 stimulation influencing SCF in the contralateral hemisphere's PPC) will be necessary.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While brain stimulation targeting specific brain areas was put forward as a tool to allow for causal neuroscience (Kuo and Nitsche, 2015), our data does not exclude such possibility, but suggests that a better understanding of local and particularly remote neurophysiological effects (e.g. as shown during cathodal M1 stimulation influencing SCF in the contralateral hemisphere's PPC) will be necessary.…”
Section: Discussionmentioning
confidence: 72%
“…A more straightforward solution would be to co-register both MEG and EEG during tDCS, the latter combination recently shown to be feasible even during online brain-machine interface (BMI) control (Soekadar et al, 2014). Accurate topographical knowledge of cortical polarity shifts during anodal or cathodal tDCS and their direction would be important to understand the causal link between area- and hemisphere-specific polarity shifts and altered brain function or behavior (Kuo and Nitsche, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Applications are multifold (Bergmann et al, 2016), ranging from studies on normal brain organization and reorganization (e.g. Fröhlich et al, 2015, Kuo et al, 2015, Prehn et al, 2015) to biomarking (e.g. by recording TMS-evoked responses in electromyography or EEG, Bortoletto et al, 2015) and the development of plasticity inducing protocols (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A mini review by Ammann et al (2016) showed that the standard tDCS montage (the current intensity (1-2 mA) and electrode size (25–35 cm 2 ) on different areas of the brain can lead to significant positive results on motor learning (Ammann et al, 2016). some studies have shown a-tDCS of the left DLPFC (with a range of current density from 0.028 to 0.1 mA/cm 2 and electrode sizes of 25–35 cm 2 ) could modify different kinds of tasks, such as implicit probabilistic classification learning (Kincses et al, 2004), sequential-letter memory tasks (Fregni et al, 2005), cognitive tasks (Kuo and Nitsche, 2015) as well as mental practice (Foerster et al, 2013). In spite of that, in line with the findings in the current study, literature also indicates that even utilization of standard intensity and electrode size is not sufficient to improve sensorimotor learning of a highly skilled tasks with a single session application in healthy participants (Butefisch et al, 2000; Boggio et al, 2006; Ni et al, 2009; Saiote et al, 2013; Minarik et al, 2015; Hashemirad et al, 2016).…”
Section: Discussionmentioning
confidence: 99%